PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS KOOPERATIF TIPE STAD PADA MATERI PERBANDINGAN UNTUK SISWA KELAS VII SMP IT ASSALAM AMBON - Jamdin, Ardon; Ratumanan, Tanwey Gerson; Laamena, Christina Martha (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2019)
This research aims to know the developing process of STAD type cooperative based on learning structure of mathematical subject; proportion meteri in the grade VII on SMPIT Assalam Ambon to achieve the valid, practical and effective learning instructional design. Learning instructional design which has been develop to student in the grade VII on SMPIT Assalam Ambon is learning Instructional devices planning, student task sheet, and student handbook. This research is a development research which used thiagrajan, semmel and semmel 4D model. The validation process of learning instructional design include competent validators on mathematics learning instructional design. Practical data analysis are achieve from observation result data of learning device and effectiveness data analysis of learning devices achieved from four sources which is 1) teacher ability of maintain the STAD type cooperative based learning. 2) students activities. 3) students responses. 4) learning results. The result of this research shows that learning devices of STAD type cooperative based learning which has been developed is valid, practical and effective